Familism and electoral outcomes: the case of French municipal elections. Issue 4 (December 2018) - Lévêque, Christophe
Abstract Politicians often rely on family members both during electoral campaigns and once elected. In France, during the 2008 and 2014 municipal elections, individuals with the same family name—a proxy for family network—are observed in approximately 40% of lists of candidates. I suggest that observing several individuals from the same family in a list may constitute a negative signal to voters about some characteristics of the (main) candidates, such as integrity, competence and responsiveness. During municipal elections, I observe that lists with homonyms obtain fewer votes than lists without homonyms (− 1.6 in the favorite specification). The effect is stronger when the list's leader (and possible future mayor) relies on her family network: such lists obtain 3.5% fewer votes. Both results hold for various empirical specifications, including models that control for lists' leader time-invariant characteristics with fixed effects.